Breastfeeding education training program for healthcare professionals: A narrative review - Rosyidah, Hanifatur; Khadka, Sabita; Sunah (Universitas Aisyiyah Yogyakarta, 2024)
Lack of knowledge and skills regarding breastfeeding education leads mothers to prefer formula milk over exclusive breastfeeding. Breastfeeding education provided by health professional is needed to support mothers to breastfeed their baby exclusively. Methodology: The methodology employed in this study was a narrative review where the researcher critically examines the ideas presented in several studies regarding breastfeeding education training program for health workers. Articles were selected using inclusion criteria: original research, published in English and Indonesian languages, within the last 5 years (2018-2023). A total of 50 articles were found. Ten articles meeting the inclusion criteria were included in the author's review. Conclusion: Breastfeeding education training programs have an impact on the success of breastfeeding mothers. The more healthcare professionals, especially midwives, understand breastfeeding education, the more breastfeeding mothers will be aware of the importance of breastfeeding for their children.